Kumar Sanjay, head of the ANC Information Bureau in Amsterdam, presents the book "Ebrahim Ismael Ebrahim versus the apartheid state" in the Amsterdam City Hall - Boersma, Pieter,
Kumar Sanjay, head of the ANC Information Bureau in Amsterdam, presents the book "Ebrahim Ismael Ebrahim versus the apartheid state" in the Amsterdam City Hall.